2019
DOI: 10.1097/md.0000000000017535
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporium spp lung infection in immunocompetent patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
5
20
0
1
Order By: Relevance
“…Our recent review revealed a delay of 5.5 months in the diagnosis of Scedosporium infection in immunocompetent patients; 16 this was much longer than the duration reported for patients with a history of near-drowning. 17 Diagnostic delays may lead to inappropriate treatment with grave consequences, even in immunocompetent patients.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Our recent review revealed a delay of 5.5 months in the diagnosis of Scedosporium infection in immunocompetent patients; 16 this was much longer than the duration reported for patients with a history of near-drowning. 17 Diagnostic delays may lead to inappropriate treatment with grave consequences, even in immunocompetent patients.…”
Section: Discussionmentioning
confidence: 68%
“…Whereas outcomes were generally dismal after voriconazole monotherapy in immunocompromised patients with S. apiospermum lung infections, the overall response was 83.3% in immunocompetent patients with S. apiospermum lung infections. 16 However, voriconazole is inhibitory, rather than fungicidal. 26,27 Voriconazole treatment was ineffective for our patient; thus, surgical resection was necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The genus Scedosporium comprises at least 10 species, of which S. apiospermum, S. boydii, S. aurantiacum and Lomentospora prolificans (formerly known as Scedosporium prolificans) are the most common species causing infections in humans. 2 Scedosporium/Lomentospora species can cause allergic bronchopulmonary mycosis, pneumonia, sinusitis, meningitis, brain abscess, arthritis, osteomyelitis, endocarditis, cutaneous and subcutaneous infections, keratitis, endophthalmitis and disseminated infection. [3][4][5] They can also colonise the respiratory tract in patients with cavitary lung disease, secondary to tuberculosis, cystic fibrosis and bronchiectasis.…”
Section: Introductionmentioning
confidence: 99%
“…boydii , S . aurantiacum and Lomentospora prolificans (formerly known as Scedosporium prolificans ) are the most common species causing infections in humans 2 . Scedosporium / Lomentospora species can cause allergic bronchopulmonary mycosis, pneumonia, sinusitis, meningitis, brain abscess, arthritis, osteomyelitis, endocarditis, cutaneous and subcutaneous infections, keratitis, endophthalmitis and disseminated infection 3–5 .…”
Section: Introductionmentioning
confidence: 99%